From north to south and back: the role of the Balkans and other southern peninsulas in the recolonization of Europe by wild boar. (22nd December 2014) - Veličković, Nevena; Djan, Mihajla; Ferreira, Eduardo; Stergar, Matija; Obreht, Dragana; Maletić, Vladimir; Fonseca, Carlos; Katinas, Liliana
Abstract Aim We analysed mitochondrial DNA (mtDNA) variation in wild boar (Sus scrofa) in the Balkans, including individuals from the northern Dinaric Balkans, an area that had not previously been characterized. Our aims were: (1) to reveal the level of genetic diversity and structuring and examine the demographic expansion of wild boar populations in the Balkans and Europe; (2) to examine the role of the Balkan gene pool in the post‐LGM (Last Glacial Maximum) recolonization of Europe; and (3) to elucidate the phylogenetic position of European and Balkan wild boar in a Eurasian context by comparing sequences of wild boar worldwide. Location Balkan Peninsula. Methods A fragment of the mtDNA control region (443 bp) was sequenced in 163 wild boar from the Balkans. Phylogenetic analyses, using MrBayes and network, were carried out together with 188 previously published sequences from the Balkan Peninsula. Phylogenetic analyses were also performed with an additional 876 wild boar sequences from around the world. Results Sixteen haplotypes were found in the new samples, including 11 not previously reported in the Balkans. Phylogenetic analyses based on all known Balkan haplotypes indicated the existence of population structuring, revealing two groups: Continental Balkans and South Balkans. The analysis of the complete dataset, comprising 1227 mtDNA sequences from wild boar sampled worldwide, revealed the presence of 168 different haplotypes. All Balkan haplotypes fell into the E1 haplogroup, except one sample that possessed an Asian haplotype. Within the E1 haplogroup, 50% of the haplotypes were unique to the Balkan Peninsula. Main conclusions Wild boar from the Balkans exhibited high genetic diversity. Similar phylogeographical patterns emerge in all southern European peninsulas, arising from post‐LGM expansion, and all three peninsulas played a similar role in the post‐glacial recolonization of Europe by wild boar. This supports a leading‐edge colonization hypothesis for all three peninsulas.